Uterine fibroids: synthesis of modern knowledge - K.D. Plaksiieva; T.F. Tatarchuk; N.V. Kosei; K.Y. Melnyk; O.S. Kozlov (Publishing House TRILIST, 2022)
Uterine fibroids is an extremely common tumor of the female reproductive system in the population. The problem of this pathology is the diversity of symptoms, mediated by the variety of sizes and locations of myomas, significant impact on reproductive function and frequent misunderstanding of the tumor nature, which leads to unwarranted hysterectomies, even among young women. Authors review the literature on the basis of modern guidelines, which reveals the potential of preserving methods of treatment of fibroids. It is also attempted to answer the most common questions about this pathology. The incidence of uterine fibroids increases with age. Fibroids are hormone dependent tumors, but the obvious cause has not yet been identified, although various risk factors are known, both modified (e.g., obesity, parity) and unmodified (race, age, etc.). Diagnosis of fibroids is simple - just an examination and ultrasound of the pelvis. Among the organ preservation methods of treatment are currently known medicinal (some of them can be used as mono-method or in combination with other methods), minimally invasive (among which stands out uterine artery embolization, as the most studied, effective and safe method) and surgical - conservative myomectomy, which can be performed by different approaches (laparoscopic, hysteroscopic or laparotomy) depending on the number and location of fibroids. This review considers the issues of fertility in uterine fibroids and after organ preservation technologies for its treatment. Differential diagnosis of uterine fibroids with leiomyosarcoma - a rare tumor and its diagnosis is quite difficult. The development of modern medical science, combining specialties with the formation of multidisciplinary teams (as in the case of collaboration with endovascular surgeons to perform uterine artery embolization) and use of an individual approach depending on the fibroids characteristics and patient needs helps reduce the proportion of hysterectomies for uterine fibroids, preservation of the organ and fertility.